SCORE LIMIT EXCESSIVE BURDENS OF TAXATION IN THE ECONOMY OF THE EU COUNTRIES AND RUSSIA - S. A. Chernogorskiy; K. V. Shvetsov (Модернизация, инновация, развитие, 2015)
In article the model of general equilibrium with taxes is considered. It is supposed that the rate of one of taxes changes and each household gains from the outside the additional income providing to it opportunity to keep in equilibrium an initial utility level. Excess tax burdens are a difference between the additional compensating income and a surplus of the fiscal duties. Their relation to a surplus of tax revenues is called as marginal excess burden MEB this tax if change of its rate is insignificant. In used model the economy is described by means of model of general equilibrium in which one product is made and one type of work is used. This model includes economic agents of three types: producer, household and state.